Physical Capacity and Activity in Patients With Idiopathic Normal Pressure Hydrocephalus - Rydja, Johanna; Kollén, Lena; Ulander, Martin; Tullberg, Mats; Lundin, Fredrik (Frontiers in Neurology, 2022)
Introduction: Most patients with idiopathic normal pressure hydrocephalus (iNPH) improve in gait after surgery. Knowledge about physical capacity and activity after shunt surgery is however limited. The aim of this study was to evaluate the effect of shunt surgery in patients with iNPH on short distance walking, functional exercise capacity, functional strength and variables of activity and sleep, three and six months postoperatively. A further aim was to evaluate the effect of a physical exercise program. Additionally we studied how changes in short distance walking correlated with functional exercise capacity and voluntary walking, respectively. Methods: In total, 127 patients were consecutively included and randomized to an exercise group (n=62) or a control group (n=65). Exercise group participants underwent a supervised 12-week exercise program. The patients were assessed before surgery, three and six months postoperatively with the 10-meter walk test (10MWT), the six-minute walk test (6MWT), the 30-second chair stand test (30sCST) and with actigraphic recordings of activity variables measured for a total of 24 hours/day during at least three days. Results: The patients improved three months postoperatively in the 10MWT (p<0.001), the 6MWT (p<0.001) and the 30sCST (p<0.001). These results remained after six months. The actigraphic recordings for voluntary walking (steps per minute) improved and nighttime sleep (%) increased after six months (p=0.01, p=0.04). There were no significant differences between the exercise group and the control group except for postoperative change in proportion of daytime sleep after three months which was slightly more reduced compared to baseline in the exercise group (p=0.04). Changes after three months in the 10MWT and the 6MWT correlated moderately (rho=-0.49, p=0.01) whereas the correlation between the 10MWT and voluntary walking was weak (rho=-0.34, p=0.01). Conclusion: Shunt surgery improved short distance walking, functional exercise capacity, functional strength and voluntary walking. An exercise program did not affect these outcomes. Short distance walking correlated weakly with voluntary walking indicating that improvement in physical capacity is not directly transferred into increased physical activity. Further research should address how interventions must be tailored to promote physical activity after shunt surgery.